Deciphering the contribution of polymer latexes on the viscoelastic behavior of hardened cement pastes by means of dynamic-mechanical analysis - Luise Göbel; Alexander Flohr; Andrea Osburg; Martin Ganß (Case Studies in Construction Materials)
The enhanced workability and durability of mortars and concretes incorporating polymer latexes have led to their increased prominence in restoration projects and engineering constructions. However, the unique viscoelastic behavior of these composite systems has restricted their widespread applications compared to unmodified equivalents. In this study, the dynamic-mechanical analysis (DMA) technique was employed to decipher the viscoelastic characteristics of polymer-modified hardened cement pastes. The impact of three different latexes and varying polymer dosages was investigated at two different sample ages. The experimental outcomes demonstrate a significant contribution of the pores formed to the elastic part of the overall viscoelastic behavior, while the glass transition temperature of the latexes is the dominating factor for the viscous part. The results also reveal that the magnitude of the contribution to the viscous properties is independent of the curing duration (7 and 28 days). Moreover, qualitative correlations were established between DMA measurements and the microstructural features of the hardened cement pastes, suggesting promising avenues for the development of tailored mix designs in practical applications of these materials.